Long-Term Efficacy of Single-Incision Laparoscopic Intragastric Resection in Treating Gastrointestinal Stromal Tumors - Umman, Veysel; Kılınçarslan, Özgür; Temel, Recep; Bağdat, Yener; Tunalı, Sarp; Ersin, Sinan; Sezer, Taylan Özgür; Fırat, Özgür (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Gastrointestinal stromal tumors (GISTs), the most common mesenchymal tumors in the gastrointestinal tract, are increasingly treated with minimally invasive surgeries. Developed techniques include laparoscopic, endoscopic, and hybrid methods for gastric GIST resection. Our study, focusing on single-incision laparoscopic intragastric resection for gastric GISTs, aims to evaluate its safety, efficacy, and long-term outcomes. Materials and Methods: In a retrospective study of GIST surgery involving 14 patients who underwent single-incision laparoscopic intragastric resections, we analyzed and compared their preoperative demographics, American Society of Anesthesiologists (ASA) scores, tumor size, neoadjuvant treatment, operation duration, hospital stay, mitotic and Ki-67 indexes, and histological features with those of patients who underwent open and laparoscopic wedge resections, to assess the impact on both survival and disease-free survival. Results: Average operation time was 93.07 minutes (range 81-120 minutes). Average blood loss: 67 +- 20 mL (range 40-110 mL). Postoperative hospital stay averaged 6.79 days (range 4-16 days). Strong correlations were observed between preoperative and pathological tumor sizes (P = .001, P < .001). Survival analysis indicated a significant association with ASA scores (P = .031), but not with mitotic index, Ki-67, or tumor size. Average survival was 80.57 months, with no recurrence or metastasis during follow-up. Conclusion: Based on our experience, the single-incision laparoscopic intragastric resection method emerges as a highly efficient, timesaving, and gentle oncological procedure, providing a safe and minimally invasive alternative resulting in shorter hospital stays and excellent long-term outcomes with minimal recurrence. For more definitive conclusions, larger, multicenter, and prospective studies are recommended. Cite this article as: Umman V, KılınÇarslan ö, Temel R, et al. Long-term efficacy of single-incision laparoscopic intragastric resection in treating gastrointestinal stromal tumors. Turk J Gastroenterol. 2024;35(3):193-203.